A spectral decomposition in one class of non-selfadjoint operators - Gubreev, G. M.; Dolgopolova, M. V.; Nedobachiy, S. I. (Methods of Functional Analysis and Topology, 2010)
In this paper, a class of special finite dimensional perturbations of Volterra operators in Hilbert spaces is investigated. The main result of the article is finding necessary and sufficient conditions for an operator in a chosen class to be similar to the orthogonal sum of a dissipative and an anti-dissipative operators with finite dimensional imaginary parts.